Water Requirement Estimation of One-Whorl Rubber (Hevea brasiliensis Müll. Arg.) Planting Materials - Cahyo, Andi Nur (Journal of Tropical Crop Science, 2021)
Fulfilling water requirement is one of the important factors for a successful production of rubber tree planting materials. Research on the irrigation requirement for young rubber trees is crucial to determine the amount of water required for an optimum plant growth. The aim of this study was to determine the amount of water needed by one whorl rubber planting material to compensate the amount of evapotranspiration, as well as to estimate the crop coefficient value (kc). The research was conducted at the Indonesian Rubber Research Institute on July 2021. Daily evapotranspiration (ETc) of rubber planting materials of clone “PB 260”, “RRIC 100”, and “IRR 112” planted in polybag size 13 cm x 35 cm were measured by weighing the planting materials daily. Evapotranspiration for the reference crop was collected from the Indonesian Rubber Research Institute climatological station. Our study showed that the amount of water required by each rubber planting material was 92.21 mL per day per polybag when the mean of daily reference evapotranspiration (ETo) was 3.67 mm per day. Therefore, the crop coefficient (kc) of one whorl rubber planting material arranged sparsely was ± 0.32. This kc value can be used as a base to calculate water requirement of one whorl rubber planting material based on the daily reference evapotranspiration (ETo).